Calibrating ecological indicator values and niche width for a Mediterranean flora. (4th March 2023) - Saatkamp, Arne; Falzon, Nicolas; Argagnon, Olivier; Noble, Virgile; Dutoit, Thierry; Meineri, Eric
Abstract: Bioindication of ecological variables such as humidity, temperature or pH by ecological indicator values of plants is a powerful tool for research in plant ecology, e.g. to detect early vegetation changes. Here, we provide a data set of ecological indicator values including niche width for an entire regional flora. We used an extensive data-base with floristic relevés from Southern France to recalibrate indicator values for light (L), temperature (T), continentality (K), air humidity (A), soil moisture (F), pH (R), productivity (N), soil texture (G), soil organic matter content (O) and salinity (S). Values were recalibrated using average values from co-occurring plants, enabling to develop indicator values for species not yet evaluated previously. Recalibrated values are on a continuous scale and we add standard deviation, median, first and third quartile for each indicator value. Linear regression of average indicator values against measured factors showed higher correlation with recalibrated values compared to original indicator values for temperature, pH and nitrogen, and comparable R 2 for moisture. Individual indicator systems performed better than a combination and applying different weighting procedures demonstrated the usefulness of inverse variance. We further illustrate graphically how recalibrated values and niche width increase ecological knowledge on plants.